Medial and extended medial gastrocnemius muscle flap: a literature review and technical approach - Breton Gutierrez, Miguel Angel; Grajeda Chavez, Obed Horacio; Herrera Uriostegui, Ismael (International Journal of Research in Medical Sciences, 2025)
Knee arthroplasty is a worldwide procedure to treat gonarthrosis, it is one of the most performed surgeries by the traumatology and orthopedics service and despite improvements in prosthetic material and refinements in surgical techniques, knee replacement complications can be devastating and can even lead to the loss of the limb. Some of these complications are mediated by factors such as diabetes mellitus, obesity, malnutrition, advanced age and smoking. Tissue loss is frequently secondary to infection or seroma and can affect 1 to 15%. If not treated promptly, the most serious complications occur. Treatment of tissue loss with muscle flaps is the most accepted therapeutic option. The objective of this article is to describe these effective techniques for the treatment of peripatellar defects secondary to complicated arthroplasties and our approach.